First transgenic trait for control of plant bugs and thrips in cotton. Issue 3 (18th December 2018) - Akbar, Waseem; Gowda, Anilkumar; Ahrens, Jeffrey E; Stelzer, Jason W; Brown, Robert S; Bollman, Scott L; Greenplate, John T; Gore, Jeffrey; Catchot, Angus L; Lorenz, Gus; Stewart, Scott D; Kerns, David L; et al.
Abstract: BACKGROUND: Plant bugs ( Lygus spp.) and thrips ( Thrips spp.) are two of the most economically important insect pest groups impacting cotton production in the USA today, but are not controlled by current transgenic cotton varieties. Thus, seed or foliar‐applied chemical insecticides are typically required to protect cotton from these pest groups. Currently, these pests are resistant to several insecticides, resulting in fewer options for economically viable management. Previous publications documented the efficacy of transgenic cotton event MON 88702 against plant bugs and thrips in limited laboratory and field studies. Here, we report results from multi‐location and multi‐year field studies demonstrating efficacy provided by MON 88702 against various levels of these pests. RESULTS: MON 88702 provided a significant reduction in numbers of Lygus nymphs and subsequent yield advantage. MON 88702 also had fewer thrips and minimal injury. The level of control demonstrated by this transgenic trait was significantly better compared with its non‐transgenic near‐isoline, DP393, receiving insecticides at current commercial rates. CONCLUSION: The level of efficacy demonstrated here suggests that MON 88702, when incorporated into existing IPM programs, could become a valuable additional tool for management of Lygus and thrips in cotton agroecosystems experiencing challenges of resistance to existing chemical control strategies. © 2018 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : The present study describes a breakthrough with regards to development of a transgenic trait for control of hemipteran and thysanopteran pests of cotton which are not sensitive to existing transgenic traits.